A thousand words about the imaging in cardiac amyloidosis (Journal of Medical Science, 2019)
Cardiac amyloidosis is an infiltrative disease which usually occurs under the form of restrictive cardiomyopathy. Advances in the treatment have changed the unfavorable outcomes of this disease. Thus, early diagnosis is essential. Recent advances in echocardiography and cardiac magnetic resonance provided new modalities for the detection of cardiac amyloidosis. This summary discusses the role of imaging techniques in the diagnosis of cardiac amyloidosis.